1460. Community-Acquired Bacteremic Pneumonia in Post-pneumococcal Vaccination Era in a Pediatric Hospital. (26th November 2018) - Gentile, Angela; Bakir, Julia; Lucion, Maria Florencia; Juarez, Maria Del Valle; Rapaport, Solana; Areso, Maria Soledad
Abstract: Background: From January 2012 PCV13 was introduced into immunization program in Argentina, 2 + 1 schedule for < 2 years. The aims of this study were to describe epidemiological-clinical pattern of community-acquired bacteremic pneumonia (CABP) in the post-vaccination period and the risks factors of CABP occurrence, complications and lethality. Methods: Cross-sectional study was performed in children with CABP diagnosis, hospitalized in Ricardo Gutierrez Children's Hospital from January 2012 to December 2017. Results: A total of 135 CABP cases were included; 63% male; 31.1% < 2 years; 75% of < 5 years received PCV13; 30.4% had underlying diseases. The pathogens isolated were ( n = 136): Streptococcus pneumoniae (Sp) 44.9% (all susceptible to Penicillin), Staphylococcus aureus (Sa) 37.5% (Methicillin-Resistant 90.2%), Haemophilus influenzae (Hi) 15.4% (33.3% nontypable Hi), Β-hemolytic Streptococci Group A 1.5% and Neisseria meningitidis 0.7%. Seventy-one percent of cases had complications (pleural effusion 63%, necrotizing pneumonia 11.1%, pneumothorax 8.1%, lung abscess 3.7%, atelectasis 0.7%). Other clinical manifestations combined with CABP were: sepsis 20%, cellulitis/abscess 9.6%, arthritis 6.7%, meningitis 5.9% and osteomyelitis 3.7%. Condensation was the predominant radiological pattern for all agents in 88.1%. Lethality rate was 3%. Sp was more associated with age ≥24 months [OR 2.78 (1.18–6.64)] and Hi was more associated with age < 24 months [OR 4.76 (1.62–14.31)]. Complications were significantly higher among Sa pneumonia cases. Children with CABP and sepsis or arthritis had higher lethality [OR 13.38 (1.14–355.45) and OR 17.71 (1.46–223.73)], respectively. Conclusion: After PCV13 introduction Sp was still the most common organism causing CABP, mainly in ≥24 months of age. Sa followed in frequency with high morbility. CABP combined with other clinical manifestations were more associated with lethality. Disclosures: All authors: No reported disclosures.